Comparative Genomics and in vitro Infection of Field Clonal Isolates of Brucella melitensis Biovar 3 Did Not Identify Signature of Host Adaptation - Holzapfel, Marion; Girault, Guillaume; Keriel, Anne; Ponsart, Claire; O’Callaghan, David; Mick, Virginie (Frontiers in Microbiology, 2018)
Brucella spp. are responsible for brucellosis, a widespread zoonosis causing reproductive disorders in animals. Species-classification within this monophyletic genus is based on bacteriological and biochemical phenotyping. Traditionally, Brucella species are reported to have a preferential, but not exclusive mammalian host. However this concept can be challenged since many Brucella species infect a wide range of animal species. Adaptation to a specific host can be a driver of pathogen variation. It is generally thought that Brucella species have highly stable and conserved genomes, however the degree of genomic variation during natural infection has not been documented. Here, we investigated potential genetic diversity and virulence of Brucella melitensis biovar 3 field isolates obtained from a single outbreak but from different host species (human, bovine, small ruminants). A unique MLVA-16 pattern suggested all isolates were clonal. Comparative genomic analyses showed an almost nonexistent genetic diversity among isolates (only one SNP; no architectural rearrangements) and did not highlight any signature specific to host adaptation. Similarly, the strains showed identical capacities to enter and replicate in an in vitro model of macrophage infection. In our study, the absence of genomic variability and similar virulence underline that B. melitensis biovar 3 is a broad-host-range pathogen without the need to adapt to different hosts.